Krapfen/dMyd88 is required for the establishment of dorsoventral pattern in the Drosophila embryo. - Charatsi, I.; Luschnig, S.; Bartoszewski, S.; Nusslein-Volhard, C.; Moussian, B. (Mechanisms of Development, 2003)
In Drosophila, the dorsoventral axis is set up by the action of the dorsal group of genes and cactus, which have been ordered genetically in a linear pathway. We have identified and characterised krapfen (kra) as a new member of the dorsal-group genes. kra encodes for the Drosophila homologue of MyD88, an adapter protein operating in the mammalian IL-1 pathway. Epistasis experiments reveal that kra acts between the receptor Toll and the cytoplasmic factor Tube. We show that there is a direct interaction between Kra and Tube presumably mediated by the death domains present in both proteins. Tube in turn interacts with its downstream effector Pelle through death domain association. We therefore suggest that upon Toll activation, Kra associates with Pelle and Tube, in an heterotrimeric complex.